Human factor and reliability analysis to prevent losses in industrial processes : an operational culture perspective /: an operational culture perspective. (2022) - Filho, Salvador Avila; de Souza Cerqueira, Ivone Conceicao; Nogueira Santino, Carine
No abstract available